2023
DOI: 10.3389/fped.2022.947340
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 3D-printed models in meetings with parents of children undergoing interventional cardiac catheterisation

Abstract: BackgroundPaediatric interventional catheterisation has consistently improved in recent decades, with often highly successful outcomes. However, progress is still required in terms of the information delivered to parents and how parental anxiety is managed.AimTo investigate the impact of cardiac printed models on improving parental understanding and alleviating anxiety before interventional catheterisation.MethodsThe parents of children undergoing interventional cardiac catheterisation were prospectively enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The researchers enrolled 75 participants and found that using 3D-printed heart models was highly effective in helping families understand their child's disease. The study also assessed, similar to this plnned study, caregiver satisfaction and found a significant improvement after the educational intervention was provided Another RCT implemented by Karsenty et al 49 with 76 patients showed that 3D heart models improve parental knowledge and reduce their anxiety level.…”
Section: Discussionmentioning
confidence: 66%
“…The researchers enrolled 75 participants and found that using 3D-printed heart models was highly effective in helping families understand their child's disease. The study also assessed, similar to this plnned study, caregiver satisfaction and found a significant improvement after the educational intervention was provided Another RCT implemented by Karsenty et al 49 with 76 patients showed that 3D heart models improve parental knowledge and reduce their anxiety level.…”
Section: Discussionmentioning
confidence: 66%
“…3D models have also been helpful in improving patients' and families' understanding of the underlying CHD anatomy and the need for a procedural intervention. [8][9][10] T A B L E 2 CHDs encountered in both "standard" and "advanced" counseling groups. In our study, we investigated the impact of 3D-printed models on parental understanding of a specific CHD during pregnancy and after the prenatal diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, beyond enhancing precision and care through 3D TOE, the utilization of 3DE may improve education and communication among practitioners and with families, particularly when employing 3D printed models ( 15 , 16 ). Although CT images have been preferred to create 3D printed models because of their high spatial resolution, improvements in 3DE images resolution now also allow for detailed 3D printed models obtained from 3DE examinations ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%